In utero low-protein-diet-programmed type 2 diabetes in adult offspring is mediated by sex hormones in rats. Issue 5 (7th August 2020) - Blesson, Chellakkan S; Schutt, Amy K; Vipin, Vidyadharan A; Tanchico, Daren T; Mathew, Pretty R; Balakrishnan, Meena; Betancourt, Ancizar; Yallampalli, Chandra
Abstract: Sex steroids regulate insulin sensitivity and glucose metabolism. We had characterized a lean type 2 diabetes (T2D) rat model using gestational low-protein (LP) diet programming. Our objective was to identify if endocrine dysfunction leading to decreased sex hormone levels will precede the development of T2D and if steroid replacement will prevent the onset of the disease. Pregnant rats were fed control or isocaloric LP diet from gestational day 4 until delivery. Normal diet was given to all mothers after delivery and to pups after weaning. LP offspring developed glucose intolerance and insulin resistance at 4 months. We measured sex steroid hormone profiles and expression of key genes involved in steroidogenesis in testis and ovary. Furthermore, one-month old rats were implanted with 90-day slow release T and E2 pellets for males and females, respectively. Glucose tolerance test (GTT) and euglycemic hyperinsulinemic clamp was performed at 4 months. LP-programmed T2D males had low T levels and females had low E2 levels due to dysregulated gene expression during steroidogenesis in gonads. GTT and euglycemic hyperinsulinemic clamp showed that LP males and females were glucose intolerant and insulin resistant; however, steroid supplementation prevented the onset of glucose intolerance and insulin resistance. Rats that developed T2D by LP programming have compromised gonadal steroidogenesis leading to low T and E2 in males and females, respectively. Sex steroid supplementation prevented the onset of glucose intolerance and insulin resistance indicating low sex steroid levels could cause compromised glucose metabolism ultimately leading to T2D. Abstract : Low-protein-programmed type 2 diabetes is mediated by testosterone and estradiol in males and females, respectively, in rats.